PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA JAMUR TIRAM UNTUK MEWUJUDKAN KEMANDIRIAN BERWIRAUSAHA DI ERA NEW NORMAL PADA KELOMPOK WANITA TANI (KWT) MAJU BERSAMA DUSUN PELEMPAT KABUPATEN LOMBOK BARAT - Mey Susanti AS; Dewi Rispawati; Basuki Srihermanto; Suryaningsih (Bajang Institute, 2021)
Indonesia reported the first case of Covid-19 on March 2, 2020. Data as of March 31, 2020 showed that there were 1.528 confirmed cases and 136 deaths. The Covid-19 death rate in Indonesia is 8.9%, the highest in Southeast Asia. After confirming the first case, the Government of Indonesia took various countermeasures to reduce the impact of the Covid-19 pandemic in various sectors. Not only the health sector but also the economic sector has suffered no less serious impacts due to this pandemic. At the family level, the small and middle levels of society become weak and decline, this is due to restrictions on community activities. Due to these conditions, it is necessary to make efforts that we must do to be able to restore the economic condition of the family by utilizing the potential that exists around it. This service was carried out at the Women Farmers Group called ‘Kelompok Wanita Tani (KWT) Maju Bersama’ Pelempat, Meninting Village, West Lombok District, West Nusa Tenggara Province. The method used in this activity is implemented in 4 (four) activity stages, namely 1) Preparation, 2) Socialization, 3) Activity Implementation, and 4) Monitoring and Evaluation. The results of the activity showed that members of Kelompok Wanita Tani (KWT) Maju Bersama have understood the technique of developing oyster mushroom cultivation and have high motivation to become entrepreneurs through cultivating oyster mushrooms as well as making it to increase people's income in the New Normal Era of the Covid-19 pandemic.